2012
DOI: 10.1007/s11033-012-1884-5
|View full text |Cite
|
Sign up to set email alerts
|

First polymorphisms in JY-1 gene in cattle (Bos taurus indicus) and their association with sexual precocity and growth traits

Abstract: Protein JY-1 is a bovine oocyte-specific protein that regulates granulosa cell function and is involved in early embryonic development, influencing the chance of pregnancy. This study investigated molecular markers for the JY-1 gene. Seven SNPs were identified in exon 3 of the gene. The positions of the SNPs in the exon and the respective substitutions are: 163 (T/C), 281 (T/C), 321 (T/C), 532 (T/C), 652 (A/G), 679 (T/C), and 722 (G/C) (GenBank: JN592587 and JF262042.2). SNP 163 is located in a coding region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The significance of the 3' untranslated region for JY-1 is not known, but based on accumulating evidence for important regulatory roles (polyadenylation, translation efficiency, localization and stability of the mRNA) of noncoding RNAs (Prasanth & Spector, 2007), a functional role for the observed mutation cannot be discounted. The regions amplified in the present study have been shown to have seven SNPs in cattle (de Camargo et al, 2012). The haplotypes of four of these SNPs were found to be correlated with sexual precocity in Nellore heifers at 8%.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…The significance of the 3' untranslated region for JY-1 is not known, but based on accumulating evidence for important regulatory roles (polyadenylation, translation efficiency, localization and stability of the mRNA) of noncoding RNAs (Prasanth & Spector, 2007), a functional role for the observed mutation cannot be discounted. The regions amplified in the present study have been shown to have seven SNPs in cattle (de Camargo et al, 2012). The haplotypes of four of these SNPs were found to be correlated with sexual precocity in Nellore heifers at 8%.…”
Section: Resultsmentioning
confidence: 49%
“…Black Begal, Barbari, Beetal, Osmanabadi and Sangamneri each contributed 48 animals, while 32 animals were of the Jakhrana breed. Two pairs of primers were utilized to amplify the exon 3 and 3'UTR of the JY-1 gene (Table 2), as reported in cattle (Camargo et al, 2012). The primers were synthesized by IDT (Integrated DNA Technologies, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Role of the 3 0 untranslated region for the JY-1 is not known, but based on accumulating evidence for important regulatory roles (polyadenylation, translation efficiency, localization, and stability of the mRNA) of noncoding RNAs [12], a functional role for the observed mutation cannot be discounted. The regions amplified in present study have been shown to have seven SNPs in cattle [2]. The haplotypes of four of these SNPs were found to be correlated with sexual precocity in Nellore heifers at 8 %.…”
Section: Resultsmentioning
confidence: 51%
“…JY-1 like sequences corresponding to 3 0 coding and untranslated region have been reported in other vertebrate species viz. human, chimpanzee, dog, mouse, and rat [2]. However, the syntenic loci do not encode for the complete JY-1 gene and lack sequences corresponding to exons 1 and 2 and thus a significant portion of the protein coding region.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that maternal-effect genes not only involved in early embryo development but also contribute to the genetic variability of reproductive traits. The association between JY-1 polymorphisms and reproductive traits such as pregnancy probability, age at first calving, and days to first calving has been characterized (de Camargo et al, 2012(de Camargo et al, , 2014. However, relatively few maternal-effect genes have been identified, and the functions and mechanisms of these genes in early embryogenesis are largely unknown.…”
Section: Q3mentioning
confidence: 99%